2014
DOI: 10.1155/2014/845438
|View full text |Cite
|
Sign up to set email alerts
|

The Role of mTOR Inhibitors in Liver Transplantation: Reviewing the Evidence

Abstract: Despite the success of liver transplantation, long-term complications remain, including de novo malignancies, metabolic syndrome, and the recurrence of hepatitis C virus (HCV) and hepatocellular carcinoma (HCC). The current mainstay of treatment, calcineurin inhibitors (CNIs), can also worsen posttransplant renal dysfunction, neurotoxicity, and diabetes. Clearly there is a need for better immunosuppressive agents that maintain similar rates of efficacy and renal function whilst minimizing adverse effects. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 91 publications
(317 reference statements)
0
38
0
Order By: Relevance
“…Although we could not directly assess these events in our study, we did observe a non-significant increase in deaths from graft failure in sirolimus users, some of which could potentially be attributable to hepatic artery thrombosis. Higher rates of hyperlipidemia and hyperglycemia have also been observed in liver recipients treated with mTOR inhibitors (24), and among kidney recipients, nephrotoxicity has been observed when sirolimus is used in conjunction with calcineurin inhibitors (25). Of note, another study that used SRTR data to assess outcomes related to sirolimus use in liver recipients, but was not restricted to HCC patients, found that sirolimus was associated with significantly higher mortality among recipients with hepatitis C infection (26).…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not directly assess these events in our study, we did observe a non-significant increase in deaths from graft failure in sirolimus users, some of which could potentially be attributable to hepatic artery thrombosis. Higher rates of hyperlipidemia and hyperglycemia have also been observed in liver recipients treated with mTOR inhibitors (24), and among kidney recipients, nephrotoxicity has been observed when sirolimus is used in conjunction with calcineurin inhibitors (25). Of note, another study that used SRTR data to assess outcomes related to sirolimus use in liver recipients, but was not restricted to HCC patients, found that sirolimus was associated with significantly higher mortality among recipients with hepatitis C infection (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, long‐term use of calcineurin inhibitor is associated with a significant risk of chronic renal impairment, de novo malignancies and recurrent hepatitis C virus . Meanwhile, accumulating evidence has recently suggested that mechanistic target of rapamycin inhibitors, such as everolimus, showed the potential not only to act against viral replication and the occurrence of malignancy, but also to alleviate nephrotoxicity by allowing calcineurin inhibitor reduction without increasing the rejection rate . Induction of such new immunosuppressants would enable a “tailor‐made” regimen to each case in the near future, hopefully facilitating to improve patient, as well as renal, outcome in HRS.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive and antiproliferative properties of EVL and its scarce nephrotoxicity and neurotoxicity suggest that it can be used as early immunosuppression after liver transplantation, especially in selected patients with a greater risk of CNI-associated toxicity or of recurrence of the hepatocarcinoma [5]. The potential benefit of the withdrawal or minimization of the CNI will be more evident the sooner it is done or if its use is avoided from the start, before the onset of any possible irreversible pathogenic changes [6].…”
Section: Discussionmentioning
confidence: 99%